Записать многочлен в стандартном виде(2x+1) (2x-1)^2 + (1-2x)^3(x^4 - 3x^2 - 3x + 3) (x^3+x^2-x)
Записать многочлен в стандартном виде
(2x+1) (2x-1)^2 + (1-2x)^3
(x^4 - 3x^2 - 3x + 3) (x^3+x^2-x)
Ответ(ы) на вопрос:
Умножаем почленно:
(x^4 - 3x^2 - 3x + 3)*(x^3 + x^2 - x) = (x^4 - 3x^2 - 3x + 3)*x^3 + (x^4 - 3x^2 - 3x + 3)*x^2 - (x^4 - 3x^2 - 3x + 3)*x =
x^7 - 3x^5 - 3x^4 + 3x^3 + x^6 - 3x^4 - 3x^3 + 3x^2 - x^5 + 3x^3 + 3x^2 - 3x =
x^7 + x^6 - 3x^5 - x^5 - 3x^4 - 3x^4 + 3x^3 - 3x^3 + 3x^3 + 3x^2 + 3x^2 - 3x =
x^7 + x^6 - 4x^5 - 6x^4 + 3x^3 + 6x^2 - 3x
(2х+1)(2х-1)^2 +(1-2х)^3 =
(2x+1)(4x^2 -2x +1) -8x^3 +12x^2 -6x +1 =
8x^3 -4x^2 -2x +1 -8x^3 +12x^2 -6x +1 =
8x^2 -8x +2
Не нашли ответ?
Похожие вопросы